Packet Filtering Based On Differentiated Services Code Point For DHCP Starvation Attacks Prevention - nfn Sarip; Arief Setyanto (BBPSDMP KOMINFO MAKASSAR, 2019)
The use of the internet today has become a necessity, the most commonly used media to connect to the internet is a Wireless LAN network. For easy access to the network, DHCP service become a standard feature that must exist, because ordinary users no longer need to think about procedures for configuring IP addresses, all of which have been done automatically by the DHCP service. But it turns out that there is a security threat to DHCP service, namely DHCP Starvation attacks that can be exhausting the availability of IP addresses in DHCP service so that the configuration of IP address automatically can no longer be done on the client. Various methods such as authentication, cryptography, and machine learning are used by researchers in preventing DHCP Starvation attacks, but the issue of effectiveness and efficiency still opens up further research opportunities. In this research, packet filtering methods based on DSCP code applied to the Netfilter system are used to do prevention of DHCP Starvation attacks, this method has proven to be very effective in making prevention and more efficient when applied on small scale wireless networks such as at office networks and internet cafe.